Systematic Literature Review on the Impact of Blended Learning to Learning Engagement and Motivation - Mulingtapang, Lourody G.; Isubol, Jay Kenneth; Lapidez, Maria Lee; Papelleras, Desiree Kate; San Juan, Ma. Grace; de Borja, Joanna Marie (Edukhasi: Jurnal Inovasi Pendidikan, 2025)
Blended learning is an instructional strategy that integrates traditional in-person training with internet resources. Unlike with traditional learning, blended learning often includes more self-paced instruction. This means that some elements are asynchronous and learners can complete their online activities tasks during times when it is most suitable for them. This research used systematic review to synthesize recent research findings on the effectiveness of blended learning in junior high school settings in the Philippines, focusing on academic outcomes such as learning engagement and motivation using the PRISMA framework. Twenty (20) articles were selected for review based on inclusion and exclusion criteria. According to the research, blended learning greatly raises student engagement by encouraging more interaction, providing flexibility, and accommodating a range of learning types with different teaching approaches. Additionally, by encouraging self-directed learning, offering immediate feedback, and raising the perceived relevance of the content, blended learning enhances both extrinsic and intrinsic motivation. Results show that respondents preferred the blended learning approach for its flexibility in accessing content online and highly adept in using digital devices. The use of e-learning tools is highly engaging and efficient; however, the blended learning model has a moderate impact on students' performance in doing activities online because learners are dependent on the answers online without even thinking at all. However, the research also draws attention to issues including technological impediments, inconsistent outcomes in various settings, and the requirement for instructor preparedness in order to execute blended learning successfully. Overall, the data show that well-designed blended learning can have a positive effect on students' motivation and engagement, providing insightful information to educators and policymakers who want to improve educational results.